2008
DOI: 10.1186/1471-2121-9-24
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of mesenchymal stem cells from C57BL/10 and mdx mice

Abstract: Background: Human mesenchymal stem cells (MSCs) have been studied and applied extensively because of their ability to self-renew and differentiate into various cell types. Since most human diseases models are murine, mouse MSCs should have been studied in detail. The mdx mouse -a Duchenne muscular dystrophy model -was produced by introducing a point mutation in the dystrophin gene. To understand the role of dystrophin in MSCs, we compared MSCs from mdx and C57BL/10 mice, focusing particularly on the aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 45 publications
5
22
0
Order By: Relevance
“…This time course is consistent with the other studies. Mouse bone marrow and lung mesenchymal progenitor cell populations demonstrate a cell cycle length of ~2-3 days [22,23], whereas a complete cell cycle for adipose-derived stromal/stem cells takes ~1.5-2.8 days in humans [2,19] and 3.3 in pigs [20]. Since cell seeding density is also considered as a factor that plays a role in the expansion capacity of MSCs, we determined doubling times of EMSCs in relation to cell plating density.…”
Section: Cfu Assaysmentioning
confidence: 99%
“…This time course is consistent with the other studies. Mouse bone marrow and lung mesenchymal progenitor cell populations demonstrate a cell cycle length of ~2-3 days [22,23], whereas a complete cell cycle for adipose-derived stromal/stem cells takes ~1.5-2.8 days in humans [2,19] and 3.3 in pigs [20]. Since cell seeding density is also considered as a factor that plays a role in the expansion capacity of MSCs, we determined doubling times of EMSCs in relation to cell plating density.…”
Section: Cfu Assaysmentioning
confidence: 99%
“…In contrast, marker molecules for the MSCs whose undifferentiation tendency is much higher than that of HSCs and EPCs are still unclear, and the expression levels of the marker molecules seem to change as they differentiate. Studies have shown that the CD34 level of MSCs or HSCs is not stable [29,30]. …”
Section: Separation Using Hydrodynamic Forcementioning
confidence: 99%
“…15,16 For example, the CD34 expression level of hematopoietic stem cells continuously decreases with developmental stage. 17 In myogenic progenitor cells, the expression level of CD34 changes during its differentiation into a myotube.…”
Section: Introductionmentioning
confidence: 99%